Pengembangan Bahan Ajar IPAS Menggunakan Model Problem-Based Learning Berbasis Aplikasi Canva di Kelas IV Sekolah Dasar - Fitri, Avisya Joel; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research aims to produce teaching materials that are valid and practical using Canva-based applications in their curriculum learning in elementary schools. The type of research used is development research (R & D) with the ADDIE model: analysis, planning, development, implementation, and evaluation. The usefulness of teaching materials is validated by validation and practicality testing of teaching materials. The subjects were grade IV students of SDN 09 Manggis Ganting and SDN Campago Guguk Bulek. The data analysis technique used a Likert scale and obtained the results of validation of teaching materials by experts and data tested the practicality of teaching materials through teacher and student response questionnaires. Data Collection Instruments consist of Validation sheets and questionnaires. Validity data was sourced from learning material experts 95%, media experts 94.64%, and linguists 93%. The average validation score is 94.21 (very valid). The practicality test was obtained through questionnaires given to teachers by 93.3% and students by 94.22%. The average practicality test result is 93.76% (very practical). Thus, the results of the study show that teaching materials that have been developed using Canva-based applications are very feasible and practical to use in elementary schools, this study recommends that teachers use innovative teaching materials.